Cyp19 expression and sex change timing in captive-bred false clownfish - J. Thamnawasolos; C. Boonphakdee (Brazilian Journal of Biology, 2023)
Abstract The false clown anemonefish (Amphiprion ocellaris) is a protandrous hermaphrodite with a distinctive reproductive behavior. This study elucidates the genetic mechanisms and timing of sex changes in captive-bred A. ocellaris by examining the expression of key genes involved in this process, specifically cyp19a1a and cyp19a1b. Gonadal histological analyses and gene expression studies were conducted on subadult fish paired for 0, 1, 2, 3, 4, 5, and 16 months. Our findings reveal that alterations in cyp19 gene expression coincide with a pairing period starting after 3 months. Both cyp19a1a and cyp19a1b expression levels were significantly elevated in paired females compared with their male counterparts and unpaired controls. Histological investigations demonstrated that sex conversion to females occurred during the 3-month pairing period. This study highlights the crucial role of cyp19a1a and cyp19a1b in the sex change process of A. ocellaris and indicates that a minimum of 5 months of pairing is necessary for completing the sex change.